Analisis Evaluasi Pelaksanaan Tugas Dinas Koperasi, Usaha Kecil Menengah, Perindustrian Dan Perdagangan Kabupaten Pelalawan - Tio Ardiyansyah; Seger sugianto; Nella suwarno (Prosiding Seminar Nasional Ilmu Manajemen Kewirausahaan dan Bisnis, 2024)
The aim of this research is to determine the evaluation of the implementation of the duties of the Department of Cooperatives, Small and Medium Enterprises, Industry and Trade of Pelalawan Regency in developing the Bono batik industry. This research was carried out by looking at the evaluation of the implementation of tasks in the development of the Bono batik industry from several points of view, namely coaching, facilitating facilities and infrastructure, and supervision. In its implementation the researcher carried out data analysis using a descriptive survey where the researcher described the actual situation of what happened. during research by collecting data, classifying and analyzing so that an analytical formulation of the problems faced can be obtained and then a conclusion can be drawn. The type of data used is primary data obtained directly from respondents, namely the Head of the Industrial Development Section and all batik craftsmen at Rumah Batik Andalan. Meanwhile, secondary data is in the form of books, official government documentation obtained from the Industrial Development Section and Rumah Batik Andalan. To collect data, researchers used questionnaires, interviews and observations. Based on the results of research conducted by researchers regarding the Evaluation of the Implementation of the Duties of the Pelalawan Regency Cooperatives, Small and Medium Enterprises, Industry and Trade Department in Industrial Development (Batik Bono Industrial Study), it can be concluded that the implementation is in the score range of 195 in the Poorly Implemented category. Which means it hasn't been implemented well.